2017
DOI: 10.1080/2162402x.2017.1299303
|View full text |Cite
|
Sign up to set email alerts
|

Immune biomarkers for prognosis and prediction of responses to immune checkpoint blockade in cutaneous melanoma

Abstract: Existing clinical, anatomopathological and molecular biomarkers fail to reliably predict the prognosis of cutaneous melanoma. Biomarkers for determining which patients receive adjuvant therapies are needed. The emergence of new technologies and the discovery of new immune populations with different prognostic values allow the immune network in the tumor to be better understood. Importantly, new molecules identified and expressed by immune cells have been shown to reduce the antitumor immune efficacy of therapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 135 publications
(189 reference statements)
0
25
0
Order By: Relevance
“…Baseline frequencies as well as an increase of the number of eosinophils between the first and the second infusion of the anti-CTLA-4 antibody ipilimumab correlate with a better overall survival (OS) [14][15][16]. Regarding therapy with anti-PD-1 antibodies, eosinophil count at baseline also correlated with OS of melanoma patients [14,17]. Additionally, recent studies by our research group revealed the prognostic value of eosinophils in melanoma patients [9].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Baseline frequencies as well as an increase of the number of eosinophils between the first and the second infusion of the anti-CTLA-4 antibody ipilimumab correlate with a better overall survival (OS) [14][15][16]. Regarding therapy with anti-PD-1 antibodies, eosinophil count at baseline also correlated with OS of melanoma patients [14,17]. Additionally, recent studies by our research group revealed the prognostic value of eosinophils in melanoma patients [9].…”
Section: Introductionmentioning
confidence: 86%
“…Eosinophil count has already been shown to be a predictive biomarker for therapy with immune checkpoint inhibitors in melanoma [14]. Baseline frequencies as well as an increase of the number of eosinophils between the first and the second infusion of the anti-CTLA-4 antibody ipilimumab correlate with a better overall survival (OS) [14][15][16]. Regarding therapy with anti-PD-1 antibodies, eosinophil count at baseline also correlated with OS of melanoma patients [14,17].…”
Section: Introductionmentioning
confidence: 99%
“…Tumor immune cell infiltration is critical in dictating melanoma patient outcome ( 82 84 ). Specific expression of chemokine/chemokine receptors and integrins is fundamental to this process and is involved in the guidance and tissue retention of immune cells.…”
Section: Chemokine Receptor Expression On Immune Cells – Decisive Rolmentioning
confidence: 99%
“…CRTH2 associated with Th2 responses would be an attractive target in melanoma as this chemokine expression is increased in patients with a multi-metastatic disease (Table 3 ). CRTH2 is also expressed on eosinophils, basophils, and some monocytes/macrophages ( 155 ), immune subsets which all convey a distinct prognosis in melanoma ( 84 , 156 ). Initially designed for targeting CRTH2 + T cells involved in respiratory diseases ( 157 , 158 ), CRTH2 antagonists could be indicated in multi-metastatic melanoma patients with high CRTH2 expression.…”
Section: Potential For Targetingmentioning
confidence: 99%
See 1 more Smart Citation